The Simpsons The complete Eighth Season Disc 1-2 - Silverman, David, 1957- (USA 20th Century Fox, 1996)
The Simpsons are very politically incorrect family. Homer works with pride in a nuclear power plant run with more regard for profit that safety. His wife is Marge, a kind of supermom. They have three kids: Bart, an underachiever ("and proud of it"), Lisa (who is as serious and responsible as Bart isn't), and Maggie.
The Simpsons is the longest-running prime-time animated show on TV! The show follows the comical adventures of the Simpson family in the town of Springfield, (the state is unknown). Homer, an unintelligent beer-drinking father who's mostly the cause of problems; Marge, the housewife mom who always tries to help the kids when they need it; Bart, the mischievous and clever 10-year-old; Lisa, the only person in Springfield who's worth becoming president of the USA; and Maggie, the baby of the family. Other characters include Apu Nahasapeemapetilon, the Hindu Kwik-E-Mart owner; Ned Flanders, the Simpsons' next-door neighbor who constantly aggravates Homer; Milhouse Van Houten, Bart's best friend and a complete coward; Mr. Burns, a extremely wealthy and evil businessman; and a huge variety of other characters. Running for 16 years, the Simpsons have connected with so many guest voices including Alec Baldwin, Kim Basinger, Mel Gibson, Tony Hawk, Elizabeth Taylor, Joe Mantegna, Lily Tomlin, Ricky Gervais, Richard Dean Anderson, James Caan, Kim Cattrall, 50 Cent, Gary Busey, Jane Kaczamrek, Lucy Liu, Robert Wagner, Amy Poehler, Stephen Hawking, Ray Romano, Albert Brooks, Fantasia Barrino, Jason Bateman, Liam Neeson, Glenn Close, Michael Moore, Ian McKellen, J.K. Rowling, Tony Blair, the Olsen Twins, and Tom Clancy.
The Simpsons is the ultimate (if very unorthodox) nuclear family. Homer, the lovable dufus father, stumbles apathetic ally through his family life and work at the local nuclear power plant. Marge, the overbearing but responsible mother, Bart, the 4th grade underachiever and nemesis to Springfield elementary's principal, Lisa, the brainy and responsible 8 year old, and Maggie, the oft-forgotten baby, round out the family. Based on a series of small cartoon sketches from the Tracy Ullman show, the Simpsons enjoy many wacky exploits in their hometown and beyond. Other characters include an incompetent lawyer, the tyrranical nuclear power plant owner, the too-perfect neighbors (the Flanders) of the Simpsons, and the less than perfect "Klown", Krusty. Colorful characters and situations abound.
Animated primetime series that follows the exploits of a hapless and semi-dysfunctional nuclear family named the Simpsons, who live in the fictional town of Springfield, whose various inhabitants add to the comedy, angst, satire and parody of this series.
The Simpsons are a dysfunctional family living in Springfield. Homer, the man of the house, is a safety inspector at the Nuclear Power Plant. Homer constantly spends most of his time at Moe's Tavern getting drunk. Marge is a hard-working housewife of three children. Bart is a clever 10 year old who loves pranking others. Lisa is the genius of the Simpson family. She recieves very excellent grades in school. She is the most trusted person in school and a "principal's pet". Maggie is the youngest. Maggie has not spoken yet. The Simpsons get themselves in some crazy adventures. In fact, they are getting in maybe about 10,000 adventures by the time the show ends in 2010.
On Your Marks, Get Set, D'Oh!
Language: English Subtitle: English
Keywords: Animation; Comedy -- TV Series